Cool and menthol receptor TRPM8 in human urinary bladder disorders and clinical correlations. - Mukerji, G; Yiangou, Y; Corcoran, S; Selmer, I; Smith, G; Benham, C; Bountra, C; Agarwal, S; Anand, P (BioMed Central, 2006)
BACKGROUND: The recent identification of the cold-menthol sensory receptor (TRPM8; CMR1), provides us with an opportunity to advance our understanding of its role in the pathophysiology of bladder dysfunction, and its potential mediation of the bladder cooling reflex. In this study, we report the distribution of the cool and menthol receptor TRPM8 in the urinary bladder in patients with overactive and painful bladder syndromes, and its relationship with clinical symptoms. METHODS: Bladder specimens obtained from patients with painful bladder syndrome (PBS, n = 16), idiopathic detrusor overactivity (IDO, n = 14), and asymptomatic microscopic hematuria (controls, n = 17), were immunostained using specific antibodies to TRPM8; nerve fibre and urothelial immunostaining were analysed using fibre counts and computerized image analysis respectively. The results of immunohistochemistry were compared between the groups and correlated with the Pain, Frequency and Urgency scores. RESULTS: TRPM8-immunoreactive staining was observed in the urothelium and nerve fibres scattered in the suburothelium. The nerve fibre staining was seen in fine-calibre axons and thick (myelinated) fibres. There was marked increase of TRPM8-immunoreactive nerve fibres in IDO (P = 0.0249) and PBS (P < 0.0001) specimens, compared with controls. A significantly higher number of TRPM8-immunoreactive axons were also seen in the IDO (P = 0.0246) and PBS (P < 0.0001) groups. Urothelial TRPM8 and TRPM8-immunoreactive thick myelinated fibres appeared unchanged in IDO and PBS. The relative density of TRPM8-immunoreactive nerve fibres significantly correlated with the Frequency (r = 0.5487, P = 0.0004) and Pain (r = 0.6582, P < 0.0001) scores, but not Urgency score. CONCLUSION: This study demonstrates increased TRPM8 in nerve fibres of overactive and painful bladders, and its relationship with clinical symptoms. TRPM8 may play a role in the symptomatology and pathophysiology of these disorders, and may provide an additional target for future overactive and painful bladder pharmacotherapy.